Feel connected to create: Self-reported psychedelic drug users exhibit higher sense of connectedness and better divergent thinking skills compared to non-users - Christian Rominger; Carolina Subow (PLoS ONE, 2025)
Psychedelic drugs can increase health, wellbeing, and even boost cognitive functions such as creativity. Beyond this, previous studies indicated that psychedelic drug intake can increase the sense of connectedness to the world, to others, and to the self. The present preregistered cross-sectional online survey investigated whether the link between psychedelic drug use and creativity (as a potential and real-life creativity) takes place due to the increased sense of connectedness in psychedelic drug users. We collected data of 326 participants (187 psychedelic users and 139 non-users), who worked on an alternate uses task and answered questionnaires assessing real-life creativity, sense of connectedness, the experience of meaningful coincidences, as well as life satisfaction and affect. In line with all preregistered hypotheses, we found that psychedelic drug users showed a higher sense of connectedness, higher creative potential (i.e., originality, fluency), and more creative activities (at a trend). Furthermore, feelings of connectedness (to the self and to the world) were associated with the originality of ideas and real-life creativity, and connectedness to the self partially mediated the difference in the originality of ideas between the psychedelic drug users and non-users. Life satisfaction and positive affect were not significantly higher in psychedelic users but were positively linked to connectedness, creativity, and to synchronicity experiences. These findings provide evidence for the association between self-reported psychedelic drug use and creativity and strengthen the role of connectedness (to the self) as a potential psychological reason why psychedelics might enhance creativity.